2013
DOI: 10.1002/tox.21885
|View full text |Cite
|
Sign up to set email alerts
|

The combined effects of DEHP and PCBs on phospholipase in the livers of mice

Abstract: Di(2-ethylhexyl) phthalate (DEHP) and polychlorinated biphenyls (PCBs) are two widely distributed pollutants that are of great concern due to their adverse health effects. However, few studies have investigated the combined effects of DEHP and PCBs. In this study, adult mice were continuously exposed to mixtures of DEHP (15 mg/kg bodyweight/day) and Aroclor 1254 (7.5 mg/kg bodyweight/day) for 12 days to investigate the combined effects of these compounds. The results showed that the ratio of the liver weight t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…It has been shown that E 2 and benzophenone-2 (weak xenoestrogen) decrease in expression of Ahr mRNA in pituitary, thyroid, and uterus female Sprague–Dawley rats (Schlecht et al 2004 ). Similar trend was observed by Lin et al ( 2015b ) where combined exposure of the mice to DEHP and Aroclor 1254 slightly but not significantly decrease expression of AhR mRNA expression in animal liver (Lin et al 2015b ). Furthermore, DEHP decrease in Cyp1a1 activity in rat liver (Seo et al 2004 ).…”
Section: Discussionsupporting
confidence: 84%
“…It has been shown that E 2 and benzophenone-2 (weak xenoestrogen) decrease in expression of Ahr mRNA in pituitary, thyroid, and uterus female Sprague–Dawley rats (Schlecht et al 2004 ). Similar trend was observed by Lin et al ( 2015b ) where combined exposure of the mice to DEHP and Aroclor 1254 slightly but not significantly decrease expression of AhR mRNA expression in animal liver (Lin et al 2015b ). Furthermore, DEHP decrease in Cyp1a1 activity in rat liver (Seo et al 2004 ).…”
Section: Discussionsupporting
confidence: 84%
“…These studies also reported significant alterations of the hepatic gene signature consistent with the liver being the primary site for detoxification (Table 1 ). Interestingly, whenever males and females have been studied, sex-differences have also been observed ( 35 , 40 , 41 ) as compiled (Table 1 ) which highlights the necessity, as mandated by the National Institutes of Health (NIH), to consider sex as a biological variable ( 49 ). Also consistent with our data ( 34 , 37 ), it was shown that the nutritional component was as well a variable to consider.…”
Section: Evidences For a Cocktail Effect From Natural Or Artificial Mmentioning
confidence: 99%
“…Other combinations of low-dosed pollutants in mixture have later been tested in mouse ( 35 , 38 , 40 ) or rat ( 41 ) models as well as in juvenile seabream ( 36 ). These studies also reported significant alterations of the hepatic gene signature consistent with the liver being the primary site for detoxification (Table 1 ).…”
Section: Evidences For a Cocktail Effect From Natural Or Artificial Mmentioning
confidence: 99%
“…Chemical mixtures extracted from natural water could also disturb the function of steroid hormones where PPARs act as key regulators [ 82 , 83 ]. In our study, cotreatment with DEHP and PCBs promoted the expression of PPAR γ but not the other PPAR types in mice liver [ 84 ].…”
Section: Environmental Chemicals As Exogenous Ligandsmentioning
confidence: 99%